2020
DOI: 10.1111/apa.15493
|View full text |Cite
|
Sign up to set email alerts
|

Schoolchildren’s experience of pain—A focus group interview study

Abstract: Aim To explore the experience of pain in 10‐ to 12‐year‐old children. Methods This interview study included students (n = 42) in grade 4‐6 in focus groups (n = 10) in southern Sweden (52% girls); mean age, 11.3 years (range 10‐12 years). The interviews were audio‐recorded and transcribed verbatim and analysed with qualitative content analysis. Results The analysis resulted in one theme: Pain as a unique experience for each individual, which was divided into five categories: (a) Feeling bodily pain; (b) Pain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Pain was the most common reason for girls (headache and stomach pain), whereas sports injuries and wounds were most common for boys. A recent focus-group study with Swedish schoolchildren found that children linked bullying, noisy school environments, grief, and remorse with headaches, stomachache, and heartache ( Persson et al, 2021 ). An interview study with school nurses from New York, USA, found that school nurses were aware that bullying was related to students with chronic health conditions, especially those with behavioral health issues ( Cohen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pain was the most common reason for girls (headache and stomach pain), whereas sports injuries and wounds were most common for boys. A recent focus-group study with Swedish schoolchildren found that children linked bullying, noisy school environments, grief, and remorse with headaches, stomachache, and heartache ( Persson et al, 2021 ). An interview study with school nurses from New York, USA, found that school nurses were aware that bullying was related to students with chronic health conditions, especially those with behavioral health issues ( Cohen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Nordic countries, school nurses often provide first‐line care for adolescents with chronic pain 10 . However, according to the school nurses themselves, the available interventions are not sufficient to treat chronic pain in adolescents 11,12 . Management of chronic pain requires a broad approach and strategies other than pharmacological treatment 13 .…”
Section: Introductionmentioning
confidence: 99%
“… 10 However, according to the school nurses themselves, the available interventions are not sufficient to treat chronic pain in adolescents. 11 , 12 Management of chronic pain requires a broad approach and strategies other than pharmacological treatment. 13 Students have requested initiatives with approaches adapted to their individual health situations and needs.…”
Section: Introductionmentioning
confidence: 99%